2003
DOI: 10.1161/01.cir.0000057811.86187.88
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Buffering Is Reduced With Age in Healthy Men

Abstract: Background-Baroreflex buffering is an important mechanism in arterial blood pressure control. The effect of healthy (physiological) aging on tonic baroreflex buffering in humans is unknown. Methods and Results-Baroreflex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
122
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(135 citation statements)
references
References 34 publications
12
122
0
1
Order By: Relevance
“…The ability of baroreflexes to "buffer" acute changes in BP under such conditions (ie, baroreflex buffering [BRB]) is reduced in certain physiological 9 and disease 10 states associated with impaired short-term BP regulation and/or altered responsiveness to vasoactive medications. In light of previous reports of less effective short-term regulation of BP in women than in men, 1,2,6,[11][12][13][14] we also hypothesized that premenopausal women have lower BRB of BP than men of similar age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of baroreflexes to "buffer" acute changes in BP under such conditions (ie, baroreflex buffering [BRB]) is reduced in certain physiological 9 and disease 10 states associated with impaired short-term BP regulation and/or altered responsiveness to vasoactive medications. In light of previous reports of less effective short-term regulation of BP in women than in men, 1,2,6,[11][12][13][14] we also hypothesized that premenopausal women have lower BRB of BP than men of similar age.…”
mentioning
confidence: 99%
“…We also measured resting sympathoadrenal activity and systemic ␣ 1 -adrenergic vascular responsiveness, 2 key determinants of these expressions of ANS control of BP, 7,9,10,15,16 to determine their potential mechanistic roles in any gender-related differences observed.…”
mentioning
confidence: 99%
“…Renal sympathetic nerve activity also has been reported to increase, but there is impaired baroreflex control of both heart rate and blood pressure (Hajduczok et al 1991). In human males, a marked decline in baroreflex buffering of blood pressure is due to, at least in part, a marked reduction in a-adrenergic receptor function (Castellani et al 1999;Jones et al 2003). Speculation on how these findings could be reconciled might include: 1) a comparison of prazosin binding in the rat parotid cell indicating a naturally occurring post-a-adrenergic receptor defect in signal transduction (Ishikawa et al 1989); 2) Age-related impairments in a-adrenergic responsiveness could be partially caused by alterations in the coupling of a-adrenergic receptors and G-proteins (Myamoto et al 1992); 3) A decline in the G protein amplification of constriction (Robert et al 1998) and 4) Competitive binding experiments (prazosin) revealed that maximal binding of the a-adrenergic receptor of the interlobar arteries is reduced 25% by 10 months of age and 50% by 18 months of age (Passmore et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, respiration makes blood pressure fluctuate with every breath (13), while physical or mental stress elevates blood pressure for minutes or even longer. The arterial baroreflex is a negativefeedback mechanism that effectively buffers such incidental blood pressure fluctuations (11,20,21,23). In negativefeedback systems, feedback delay often causes resonance in a given frequency band; this is the price to be paid for effective buffering at other frequencies.…”
mentioning
confidence: 99%